Topographical distribution of Aβ predicts progression to dementia in Aβ positive mild cognitive impairment. Issue 1 (21st June 2020) - Pascoal, Tharick A.; Therriault, Joseph; Mathotaarachchi, Sulantha; Kang, Min Su; Shin, Monica; Benedet, Andrea L.; Chamoun, Mira; Tissot, Cecile; Lussier, Firoza; Mohaddes, Sara; Soucy, Jean‐Paul; Massarweh, Gassan; et al.
Abstract: Introduction: Abnormal brain amyloid beta (Aβ) is typically assessed in vivo using global concentrations from cerebrospinal fluid and positron emission tomography (PET). However, it is unknown whether the assessment of the topographical distribution of Aβ pathology can provide additional information to identify, among global Aβ positive individuals, those destined for dementia. Methods: We studied 260 amnestic mild cognitive impairment (MCI) subjects who were Aβ‐PET positive with [ 18 F]florbetapir. Using [ 18 F]florbetapir, we assessed the percentage of voxels sowing Aβ abnormality as well as the standardized uptake value ratio (SUVR) values across brain regions. Regressions tested the predictive effect of Aβ on progression to dementia over 2 years. Results: Neither global nor regional [ 18 F]florbetapir SUVR concentrations predicted progression to dementia. In contrast, the spatial extent of Aβ pathology in regions comprising the default mode network was highly associated with the development of dementia over 2 years. Discussion: These results highlight that the regional distribution of Aβ abnormality may provide important complementary information at an individual level regarding the likelihood of Aβ positive MCI to progress to dementia.